Admission Glucose Level Predicts In-hospital Mortality in Patients with Acute Pulmonary Embolism Who Were Treated with Thrombolytic Therapy - ÇİNÇİN, AHMET ALTUĞ; ATAŞ, HALİL (SPRINGER, 2016)
Elevated admission serum glucose level is associated with unfavourable clinical outcomes in various clinical conditions. The aim of this study was to investigate the relationship between admission glucose levels and in-hospital and long-term adverse clinical outcomes in patients with pulmonary embolism (PE) treated with thrombolytic therapy. A total of 183 consecutive confirmed acute PE patients (98 female and 85 male; mean age 61.9 +/- A 15.7 years) who were treated with thrombolytic therapy enrolled in this study. The study population was categorised into four quartiles according to admission serum glucose levels (group I: glucose a parts per thousand currency sign115 mg/dl; group II: glucose > 115-141 mg/dl; group III: glucose > 141-195 mg/dl; and group IV: glucose a parts per thousand yen196 mg/dl). In-hospital mortality was significantly higher in group IV (28.8 %) compared to group III (15.2 %), group II (6.6 %), and group I (2.1 %) (p < 0.001). In multivariate analysis, admission glucose level (OR 1.013, 95 % CI 1.004-1.021, p = 0.004) and admission anaemia (OR 0.602, 95 % CI 0.380-0.955, p = 0.03) were independent predictors of in-hospital mortality. The mean follow-up period was 34 months. During long-term follow-up, all-cause mortality, recurrent PE, major and minor bleeding were similar among the four groups. Admission glucose level is a simple, inexpensive, easily available, and effective laboratory parameter for predicting in-hospital mortality in patients with PE.
Keywords: Pulmonary embolism; Glucose; Thrombolytic therapy; Mortality; Clinical outcomes; HYPERGLYCEMIA PREDICTS; DIABETES-MELLITUS; EUROPEAN-SOCIETY; STROKE PATIENTS; HEART-FAILURE; TASK-FORCE; DIAGNOSIS; GUIDELINES; METAANALYSIS; MANAGEMENT